1984
DOI: 10.1177/036354658401200504
|View full text |Cite
|
Sign up to set email alerts
|

The snapping hip syndrome

Abstract: The snapping hip syndrome is a symptom complex characterized by hip pain and an audible snapping of the hip with exercise typically seen in young individuals. "External" and "internal" etiologies have been described, although the "internal" etiology is poorly understood. A clinical, radiographic, and anatomical study of eight patients with this disorder, secondary to an internal etiology, was undertaken to aid in the diagnosis and surgical treatment. Iliopsoas bursography with cineradiography revealed subluxat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
143
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(147 citation statements)
references
References 7 publications
2
143
0
2
Order By: Relevance
“…Hussain et al 4 have reported femoral acetabular impingement secondary to osteochondroma. Schaberg et al 5 have reported two cases of internal snapping hip due to proximal femur exostosis. Sanshiro et al 6 have reported a case of external snapping hip caused by exostosis of proximal femur.…”
Section: Discussionmentioning
confidence: 99%
“…Hussain et al 4 have reported femoral acetabular impingement secondary to osteochondroma. Schaberg et al 5 have reported two cases of internal snapping hip due to proximal femur exostosis. Sanshiro et al 6 have reported a case of external snapping hip caused by exostosis of proximal femur.…”
Section: Discussionmentioning
confidence: 99%
“…The internal type of extraarticular snapping is the iliopsoas tendon slipping over the iliopectineal eminence. Other causes include iliopsoas bursa slipping of the iliofemoral ligament over the femoral head and slipping of the long head of the biceps femoris tendon over the ischial tuberosity (1,(6)(7)(8)(9)(10) Mayer insisted that the major factors of snapping hip syndrome were abnormality of the fascia lata that forms the catch back of the posterior greater trochanter, unusual prominency of the trochanter, abnormal relaxation of the gluteus maximus muscle and irregularities of the acetabulum (8). In addition to the fascia lata being the cause, there has been a reported case that developed snapping hip syndrome due to a band of fibrous tissue that corresponded to a portion of the gluteus maximus muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Offene Verfahren zeigten Komplikationsraten bis zu 40% wie Rezidive, eine bleibende Schwäche der Hüftbeugung und Parästhesien im ventralen Oberschenkel [1,23,34,45]. Byrd [8,9] …”
Section: Psoassehnentendinitis Und Schmerzhaftes Springen Der Psoassehneunclassified